Pengembangan Manajemen Pengetahuan Madrasah & Pesantren: (Studi Kasus Pondok Pesantren Modern As-Salam Surakarta) - Hartono Hartono; Mujazin Mujazin (Universitas Palangka Raya, 2024)
The rapid advancement of science and technology in the global era is currently felt in various fields of community life, especially in the fields of education, social and culture, including in boarding school education. In order to face the demands of society, community educational institutions including Islamic boarding schools must be functional, because educational institutions as a forum in society can be used as a gateway in facing the demands of society, science and technology that continue to change. Therefore, in order to become an ideal boarding school, it is necessary to organize the management and development of the boarding school. Islamic boarding school as one of the educational institutions that combines these three aspects, not only emphasizes the cognitive intelligence aspect, but also emphasizes the affective and psychomotor aspects, namely by teaching values and norms in accordance with Islamic law and equipping students with various skills (life skills). The development of management and management of education at PPMI Assalam consists of management elements including man, money, material, method, macine, and market. While the realization steps in order to implement the program are planning, organizing, implementing, and monitoring.